Critical analysis of the efficacy of the ReCAAP in combating piracy and armed robbery against ship in Asdia - Win, Kyaw Hla; Ansari, Abdul Haseeb; Masum, Ahmad; Eishan Jan, Mohammad Naqib (The Indian Law Institute, New Delhi, India, 2016)
The Regional cooperation agreement on combating piracy and armed robbery against ships in Asia 2004 is an important regional agreement for alleviating incidents of piracy and armed robbery against ships and all the member states are sincerely enforcing its treaty norms through appropriate national legislations. However, the agreement has failed to achieve considerable success because the two major players, Malaysia and Indonesia, of the navigation industry have yet to accept its membership, and also because the definition of maritime crimes in the agreement is not wide enough to encompass all kinds of maritime crimes pertaining to piracy and armed robbery. Because of these and some other deficiencies, it becomes necessary to critically examine the agreement and to offer necessary viable suggestions. The paper undertakes this task and suggests that the two states should be persuaded to be members of the agreement. It further designs a workable definition to the term ‘maritime crimes’ so that the objectives of the agreement are achieved.